Enantiomer-specific accumulation and depuration of α-hexabromocyclododecane (α-HBCDD) in chicken (Gallus gallus) as a tool to identify contamination sources. (August 2017) - Omer, Elsa; Cariou, Ronan; Huneau-Salaün, Adeline; Dervilly-Pinel, Gaud; Baéza, Élisabeth; Travel, Angélique; Le Bouquin, Sophie; Jondreville, Catherine; Le Bizec, Bruno
Abstract: A LC-ESI(−)-HRMS method dedicated to the analysis of 6 HBCDD enantiomers at trace levels in animal matrices was developed, using a cellulose based stationary phase with a particle size of 2.5 μm. This method was applied to a sample set derived from a kinetic study of α-HBCDD previously conducted in fast- and slow-growing chickens ( Gallus gallus domesticus, n = 49, plus controls), in order to study the enantiomer specific accumulation and depuration of α-HBCDD in various tissues. Regarding abdominal adipose tissue, muscle and liver, the average enantiomeric fractions of α-HBCDD (EFα ) for continuously exposed groups ranged between 0.434 and 0.467, with standard deviations below 0.014, showing a significant enrichment in (−)α enantiomer even accentuated for slow growing individuals during depuration with EFα reduced by about 0.020. Similar trends were observed for pooled plasma. Then, EFα of circulating plasma α-HBCDD appeared to closely reflect EFα in storage tissues and liver, suggesting some equilibrium. The racemic elimination of α enantiomer in excreta during the contamination phase indicated that no preferential gastrointestinal absorption took place. By contrast, preferential excretion of (−)α-HBCDD from the circulating compartment to the intestinal lumen occurred during the depuration. Finally, the method was applied to samples collected in three chicken farms, selected for total HBCDD levels in muscle in the ng/g range, as a tool to determine whether the contamination occurred ante- or post-mortem, according to the chiral signature. Ante-mortem contamination was hypothesised for 2 farms, with feed being excluded as contamination source. Graphical abstract: Highlights: A LC-ESI-HRMS method dedicated to the analysis of HBCDD enantiomers was developed. A 2.5 μm particle diameter chiral column was used for separation. Ante-mortem exposure of chickens to α-HBCDD leads to (−)α-HBCDD specific enrichment. Survey on chicken meat French production shown quite low HBCDD contamination levels. Enantiomeric profiles helped investigation of sources in the 3 most polluted farms.